Impact of Training on Improving Proper Handwashing Practices among Elementary School Students - Huthamaputiran, Theruna; Sudigdoadi, Sunarjati; Purnama, Andriana (Althea Medical Journal, 2017)
Background: Hand washing is among the most effective ways to prevent diseases. In Indonesia, only a quarter of the entire population practice proper handwashing techniques. Of these, children are the most vulnerable group for contracting diseases. Nevertheless, they also are crucial agent for behavior transformation as they are keen and open to new ideas. Therefore, this study was conducted to determine if training would have an improvement on a proper hand washing practices among elementary school students.Methods:An observational descriptive study design using random sampling was conducted from September to November 2013 in Jatinangor Subdistrict, West Java, Indonesia using primary data of one hundred elementary school students from four elementary schools. Questionnaires were given after informed consent. A demonstration on hand washing techniques and education on proper hand washing practices was then given. Two weeks later, the same questionnaire was given to measure the influence of the training. The collected data were presented using frequency tabulation.Results: Before the training on proper hand washing practices was conducted, only 86.9% students were practicing it properly. After the training was given, 90.7% of the students were doing it properly. For the hand washing technique, only 66.8% of students knew the correct steps before the intervention was given and 78.7% students did them correctly after the intervention.Conclusions:The training shows an overall improvement on the studentsâ hand washing practices.Â DOI:Â 10.15850/amj.v4n2.1073